Tuning the Electrical State of 2DEG at LaVO3−KTaO3 Interface: Effect of Light and Electrostatic Gate. Issue 16 (17th June 2020) - Goyal, Saveena; Wadehra, Neha; Chakraverty, Suvankar
Abstract: Two‐dimensional electron gas (2DEG) formed at the interface of perovskite oxides has drawn considerable interest due to its rich underlying physics and potential in future generation spin‐electronic devices. Electrostatic gating and light illumination are two frequently applied stimuli for such devices. In this work, electrical conductivity tuning of a recently discovered conducting interface of crystalline LaVO3 and KTaO3 (LVO−KTO) is reported through electrostatic gating as well as light illumination. Signature of significant photoconductivity as well as persistent photocurrent is observed. A giant enhancement of resistance is found to occur under light illumination when a negative electrostatic gate bias ( V G > −8 V) is applied. These effects offer a possible control on carrier density of the oxide interface, which is otherwise difficult due to their huge intrinsic carrier density. Further, a protocol deploying light and gate bias in an appropriate sequence is demonstrated to use this interface as a possible optical‐switch or memory storage device. Abstract : The recently discovered conducting interface of LaVO3 −KTaO3 exhibits interesting behaviour under the influence of light and electrostatic gating. Photocurrent persists even after the withdrawal of light. A large enhancement in resistance is observed under the combined effect of negative gate voltage and light. The potential of this interface as a memory device is demonstrated by deploying light‐gate in an appropriate sequence.